The Relationship Between Human Resource Flexibility And Performance Indicators Among Hospitals Of Islamic Azad University - Seyed Jamallodin Tabibi; Mahmoud Reza Gohari; Elham Gholami (Tehran University of Medical Sciences, 2016)
Background and Aim: The study of human resources flexibility impact on hospitals performance indicators can be effective on hospitals performance improvements. The main purpose of this research is to investigate the relationship between human resources flexibility and hospitals’ performance indicators of Islamic Azad University. Materials and Methods: The present research was a descriptive-analytical research that has been induced cross-sectionally in 2013. The statistical sampling has been selected randomly, and class assignment among 108 nurses, and supportive employees in five hospitals of Islamic Azad University. Data collection tools was hospital’s performance indicator forms, and flexibility questionnaire based on Right and Esnel. The process of data analysis has been done using SPSS software and by descriptive statistical indicators and correlation tests. Results: The studied employees had low flexibility. The total studied hospitals were in undesirable situation from the perspective view of bed occupying and bed rotation ratio. Finally, there were not any meaningful relationship between human resources flexibility and hospitals performance indicators. Conclusion: According to low flexibility of human resources of Islamic Azad University hospitals, the policies should be made in order to coordinate human resources process  with human  resources  flexibility strategies. Furthermore, human resource for the purpose of creating flexibility and hospital subsidiaries of Islamic Azad University performance improvements could be clearly effective in such hospitals situation promotion.